Hopes for a better (techno) future - Korjonen‐Kuusipuro, Kristiina; Wojciechowski, Adam (Human Technology, 2023)
During the last few months, we have seen plenty of discussion about text-generating AI chatbots like ChatGPT. We have also seen many different kinds of affects and emotions connected to these tools. People are curious, suspicious, intrigued, or maybe even afraid of what our future will be like. Therefore, we need hope. In this editorial we want to stress the importance of hope and argue that people should not be left alone with suspicion, fear and doubt about how technology will change their future.